Development and validation of the ISARIC 4C Deterioration model for adults hospitalised with COVID-19: a prospective cohort study - Gupta, RK; Harrison, EM; Ho, A; Docherty, AB; Knight, SR; van Smeden, M; Abubakar, I; Lipman, M; Quartagno, M; Pius, R; Buchan, I; Carson, G; et al. (Elsevier, 2021)
BACKGROUND: Prognostic models to predict the risk of clinical deterioration in acute COVID-19 cases are urgently required to inform clinical management decisions.